Writers and liars : a novel - Goodman, Carol (William Morrow, an imprint of HarperCollinsPublishers, 2025)
A group of mystery authors gathers on a secluded Greek island for a writer's retreat, only to discover that their enigmatic host has been murdered and everyone present is a suspect.